2017
DOI: 10.15641/jcbm.1.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management in the Nigerian Construction Firms: Practices and Challenges

Abstract: Improvement of human resource management is critical to overall productivity and cost effectiveness in the construction industry. This study assesses the current human resource management practices in the Nigeria construction organisation and the challenges confronting it. Questionnaire survey was adopted using purposive sampling technique. Ninety eight human resource managers and construction professionals in two categories of construction organisations (client organisations involved in real estate developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…For example, in Malaysia, Othman et al (2012) noted that amongst other issues, insufficient training of employees tends to hamper the effectiveness of HRM practices. A similar observation has been made in India (Samuel and Timmaraju, 2015), Iran (Tabassi and Abu Bakar, 2009) and Nigeria (Ameh and Daniel, 2017). To improve the training of the workforce, both short-term and long-term training of construction workers and government support through the provision of incentives or policies that will encourage self-learning through certification of fitness for occupation in the project has been suggested (Tabassi and Abu Bakar, 2009).…”
Section: Workforce Management In the Construction Industrysupporting
confidence: 80%
See 1 more Smart Citation
“…For example, in Malaysia, Othman et al (2012) noted that amongst other issues, insufficient training of employees tends to hamper the effectiveness of HRM practices. A similar observation has been made in India (Samuel and Timmaraju, 2015), Iran (Tabassi and Abu Bakar, 2009) and Nigeria (Ameh and Daniel, 2017). To improve the training of the workforce, both short-term and long-term training of construction workers and government support through the provision of incentives or policies that will encourage self-learning through certification of fitness for occupation in the project has been suggested (Tabassi and Abu Bakar, 2009).…”
Section: Workforce Management In the Construction Industrysupporting
confidence: 80%
“…Furthermore, Hanif and Imran (2017) mentioned that issues surrounding training and retaining skilled workers are a critical challenge in India's construction industry. Ameh and Daniel (2017) have noted that HRM is challenged by the high employee turnover that has characterised most developing countries' construction industries. In South Africa, Nkomo and Thwala (2009) concluded that there is a high rate of labour turnover.…”
Section: Employee-related Challengesmentioning
confidence: 99%
“…The author further reiterated that the development of quality, functional and adequate skills and competencies is one of the features of business education programme. In the same vein, Ameh and Barinem (2016) argued that business education is in dire need of effective and efficient evaluation that can assist in bridging the discrepancies between the theory and practice. Similarly, Ajunwo (2017) posits that there is need for taking practical steps in teaching business education students with the view to acquire the necessary competencies of operating relevant software applications in the business world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the construction industry originally contributed between 5.8% of the Nigeria GDP in the 1980s, before it declined to 1.4 in 2010 and 4% in its current state in (Oluwakiyesi, 2011;Ihua-Maduenyi, 2018). The decrease in the contribution to the nation's GDP is due to several factors, which includes inadequate training and skills development, motivation and labour relation practices, poor planning, problems of finance, corruption, recruitment, and selection practices (Oseghale, et al, 2015;Tunji-Olayeni, et al, 2017;Ameh & Daniel, 2017). More so, the rate at which buildings collapse in Nigeria today is increasing daily and sadly to say that this failure in some of the buildings occur during construction work and use, which needs immediate attention (Egunjobi & Adebayo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has affected the performances of the industry which led to low and consistently poor productivity over the years. In addition, the quality of workers' skills is another pressing issue in the Nigerian construction industry and is already having serious implications for both the industry and the Nation's economy (Oseghale, et al, 2015;Ameh & Daniel, 2017). There are several studies addressed the impact of training and skills development on the output of the construction industry in Nigeria.…”
Section: Introductionmentioning
confidence: 99%